Effect of sodium citrate ingestion on metabolism and 1500 m running performance in young female runners - Ööpik, V.; Timpmann, S.; Medijainen, L.; Karelson, K.; Kelve, K. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the present study was to assess the effects of sodium citrate administration before exercise on metabolism and performance in 1500 m run in young female runners in field conditions. The results of the present study demonstrate the importance of maintaining fluid balance before 1500 m run in young female runners. However, inclusion of sodium citrate in amount of 0.4 g·kg-1 bm into fluids consumed before race does not give any additional effect on performance. The higher lactate concentration measured in plasma of the subjects after the run in the CIT trial compared with CON and PLC conditions is most likely caused by increased contribution of anaerobic glucolysis to energy production after citrate consumption.